Cell Derived Matrix Fibulin-1 Associates With Epidermal Growth Factor Receptor to Inhibit Its Activation, Localization and Function in Lung Cancer Calu-1 Cells - Harikrishnan, Keerthi; Joshi, Omkar; Madangirikar, Saili; Balasubramanian, Nagaraj (Frontiers in Cell and Developmental Biology, 2020)
Epidermal Growth Factor Receptor (EGFR) is a known promoter of tumor progression and is overexpressed in lung cancers. Growth factor receptors (including EGFR) are known to interact with extracellular matrix (ECM) proteins, which regulates their activation and function. Fibulin-1 (FBLN1) is a major component of the ECM in lung tissue, and its levels are known to be downregulated in non-small cell lung cancer (NSCLC). To test the possible role FBLN1 could have in regulating EGFR signaling and function in lung cancer, we performed siRNA mediated knockdown of FBLN1 isoforms FBLN1C and FBLN1D in NSCLC cell line (Calu-1). Their loss significantly increased basal and EGF (Epidermal Growth Factor) mediated EGFR activation without affecting net EGFR levels. Overexpression of FBLN1C and FBLN1D accordingly inhibits EGFR activation in Calu-1 cells. FBLN1C and FBLN1D mediated EGFR activation promotes cell migration in wound healing assays, confirmed by Erlotinib treatment. Mechanistically, both FBLN1 isoforms interact with EGFR, though their association is not dependent on its activation. Notably, this association is also detected in cell-derived matrix (CDM). Calu-1 cells plated on CDM derived from FBLN1C and FBLN1D knockdown cells show a significant increase in EGF mediated EGFR activation. This promotes cell adhesion and the spatial localization of phosphorylated EGFR (Y1173) at membrane ruffles to drive cell spreading on knockdown CDMs, which is lost on Erlotinib mediated EGFR inhibition. Together, these findings show that FBLN1, as part of the ECM, can bind and regulate EGFR activation and function in NSCLC cells, further highlighting the role tumor ECM microenvironment has in influencing EGFR dependent lung cancers.